Memories of the Assyrian Exile in Persian-Period Yehud: A View from Chronicles and Ezra-Nehemiah - Leṿin, Yigʾal (Hebrew bible and ancient Israel, 2022)
The conquest and exile of Israel and the long subjugation of Judah by Assyria seems to have made a huge impression on the people of Judah, as can be seen in the relative biblical literature. Judah, however, actually outlived Assyria, only to fall to Babylon. This paper examines the ways in which Assyria is represented in the post-exilic biblical literature, as a reflection of the way in which it was remembered by the people of Yehud in the Persian Period. Our conclusion is that Assyria did not seem to occupy a very prominent place in post-exilic Judahite thought. It was part of »ancient history,« not a part of daily life, and not even part of very recent history. The writers of the Persian Period had more recent traumas with which to deal.